Effect of nanostructured MgO directly grown on pure magnesium substrate on its in vitro corrosion and bioactivity behaviour - Majid Shahsanaei; Masoud Atapour; Morteza Shamanian; Nastaran Farahbakhsh; Swathi N.V. Raghu; Torsten Kowald; Sybille Krauß; Seyedsina Hejazi; Shiva Mohajernia; Manuela S. Killian (Journal of Magnesium and Alloys)
This study introduces a nanostructured MgO coating fabricated via anodization in a non-aqueous electrolyte, offering a novel approach to addressing the challenges of corrosion resistance and biofunctionality. The surface was characterized before and after immersion testing using field emission scanning electron microscopy (FESEM), energy-dispersive X-ray spectroscopy (EDX), and X-ray diffraction (XRD). Electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization tests demonstrated a 2-fold reduction in the corrosion resistance compared to untreated magnesium. Biomineralization studies demonstrated the uniform formation of apatite with a Ca/P ratio of 1.35 on the nanostructured surface after 14 days in simulated body fluid (SBF), surpassing that of microstructured MgO. Hydrogen evolution decreased from 912±38 µL cm-2 for untreated Mg to 615±32 µL cm-2 for the Mg/MgO nanostructure and 545±29 µL cm-2 for the Mg/MgO/HA sample. These findings highlight the potential of nanostructured MgO coatings to advance Mg-based implants by providing enhanced corrosion protection, improved biomineralization, reduced hemolysis and increased cell viability, and reduced H2 generation.